CEO gender and employee relations: Evidence from labor lawsuits - Liu, Chelsea (Journal of banking & finance, 2021)
•This study examines the relationship between CEO gender and firms’ employee relations.•Firms led by female CEOs experience significantly fewer labor lawsuits.•Firms with female CEOs encounter fewer serious allegations of coercive labor practices.•The presence of female CEOs is associated with a greater variety of employee-friendly initiatives adopted by their firms. This study investigates the relationship between the gender of chief executive officers (CEOs) and firms’ employee relations, as proxied by labor lawsuits. Drawing on gender socialization, upper echelons, and stakeholder theories, this study hypothesizes that firms with female CEOs have superior employee relations. Using a hand-collected sample of 11,970 labor lawsuits filed against Standard & Poor's 1500 firms from 2001–2014, the empirical results show that firms led by female CEOs experience fewer labor lawsuits. The findings are robust to a series of additional analyses to alleviate endogeneity concerns. The evidence from this study provides novel insights into the role of female corporate leaders in the context of employee relations.